Large-amplitude acoustic solitary waves in a Yukawa chain. (13th June 2017) - Sheridan, T. E.; Gallagher, James C.
Abstract : We experimentally study the excitation and propagation of acoustic solitary waves in a one-dimensional dusty plasma (i.e. a Yukawa chain) with n=65 particles interacting through a screened Coulomb potential. The lattice constant a=1.02± 0.02 mm. Waves are launched by applying a 100 mW laser pulse to one end of the chain for laser pulse durations from 0.10 to 2.0 s. We observe damped solitary waves which propagate for distances 30a with an acoustic speed c_s=11.5± 0.2 mm s^-1 . The maximum velocity perturbation increases with laser pulse duration for durations 0.5 s and then saturates at ≈15 % . The wave speed is found to be independent of the maximum amplitude, indicating that the formation of nonlinear solitons is prevented by neutral-gas damping.